Deteksi Kekasaran Permukaan Nugget Weld Dengan Menggunakan Aplikasi Terhadap Hasil Pengelasan Rsw pada Plat Stainless Steel 304 - Fitrah, Muhammad Aqdar; Utami, Hermin Hardyanti (Universitas Negeri Makassar, 2023)
Resistance Spot Welding (RSW) is welding process that is widely used in the automotive industry such as the manufacture of vehicle bodies. This study aims to measure the level of roughness in stainless steel grade 304 with the RSW Welding method. In this study, Gwyddion software was used to measure the roughness of stainless steel grade 304. This study used variations in electric current, which are 5kA and 7kA, with a pressure of 3 bar and 9 seconds with 100 x 25 mm for the size. Furthermore, for each electric current there are 3 specimens and macro photo tests are carried out then the roughness values for 5kA is 153 µm, 151 µm, and 150 µm. Moreover, the rough values of 7kA is 133 µm, 135 µm and 101 µm. From the results, it was found that the higher of welding current, the smoother of the roughness of the nugget weld. This is because the heat that enters the nugget weld undergoes a good maturation process.